(untitled) (CIPEEX, 2025)
Understanding the acute and chronic phases of a disease is critical to the proper management of various medical conditions. The acute phase is characterized by the sudden onset of symptoms, with intense and often severe manifestations. During this period, the body reacts quickly, usually with an inflammatory response, with the aim of fighting the disease or injury. Treatment is usually focused on relieving symptoms and controlling the disease. In contrast, the chronic phase develops when the condition persists over time, and can last for months or even years, often after the acute phase. At this stage, symptoms may be less intense, but they are prolonged and often recurring, requiring ongoing management, requiring prolonged treatment to manage the condition and prevent complications. Chronicity can result from an unresolved acute phase or from conditions that naturally evolve into a chronic state. The transition from an acute to a chronic phase may occur due to an incomplete resolution of the initial phase or the nature of the disease, which tends to be prolonged. Understanding the acute and chronic phases of a disease is essential for developing effective treatment strategies and improving patients’ quality of life.